Site-Specific Modification Using the 2'-Methoxyethyl Group Improves the Specificity and Activity of siRNAs - Xinyun Song; Xiaoxia Wang; Yuan Ma; Zicai Liang; Zhenjun Yang; Huiqing Cao (Elsevier, 2017)
Rapid progress has been made toward small interfering RNA (siRNA)-based therapy for human disorders, but rationally optimizing siRNAs for high specificity and potent silencing remains a challenge. In this study, we explored the effect of chemical modification at the cleavage site of siRNAs. We found that modifications at positions 9 and 10 markedly reduced the silencing potency of the unmodified strand of siRNAs but were well tolerated by the modified strand. Intriguingly, addition of the 2'-methoxyethyl (MOE) group at the cleavage site improved both the specificity and silencing activity of siRNAs by facilitating the oriented RNA-induced silencing complex (RISC) loading of the modified strand. Furthermore, we combined MOE modifications at positions 9 and 10 of one strand together with 2'-O-methylation (OMe) at position 14 of the other strand and found a synergistic effect that improved the specificity of siRNAs. The surprisingly beneficial effect of the combined modification was validated using siRNA-targeting endogenous gene intercellular adhesion molecule 1 (ICAM1). We found that the combined modifications eliminated its off-target effects. In conclusion, we established effective strategies to optimize siRNAs using site-specific MOE modifications. The findings may allow the creation of superior siRNAs for therapy in terms of activity and specificity.